2(x-4)+3(2-x)+2x+2=

Simple and best practice solution for 2(x-4)+3(2-x)+2x+2= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-4)+3(2-x)+2x+2= equation:


Simplifying
2(x + -4) + 3(2 + -1x) + 2x + 2 = 0

Reorder the terms:
2(-4 + x) + 3(2 + -1x) + 2x + 2 = 0
(-4 * 2 + x * 2) + 3(2 + -1x) + 2x + 2 = 0
(-8 + 2x) + 3(2 + -1x) + 2x + 2 = 0
-8 + 2x + (2 * 3 + -1x * 3) + 2x + 2 = 0
-8 + 2x + (6 + -3x) + 2x + 2 = 0

Reorder the terms:
-8 + 6 + 2 + 2x + -3x + 2x = 0

Combine like terms: -8 + 6 = -2
-2 + 2 + 2x + -3x + 2x = 0

Combine like terms: -2 + 2 = 0
0 + 2x + -3x + 2x = 0
2x + -3x + 2x = 0

Combine like terms: 2x + -3x = -1x
-1x + 2x = 0

Combine like terms: -1x + 2x = 1x
1x = 0

Solving
1x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '1'.
x = 0

Simplifying
x = 0

See similar equations:

| 7(2l+8)=122 | | 2x-45=90 | | X^5=230 | | x^3-27x^2+12=0 | | 0.43=0.0814ln(x)+0.3357 | | 3sin(x)-2cos(x)=0 | | a-2a-3=0 | | -3y=5t | | x+10-16=1 | | 3*b-b*(-3)+3*(-b)= | | 3X-21=4X-36 | | Ln*(x-4)+ln*(x-7)=ln*18 | | 3xb-bx(-3)+3x(-b)= | | 1/3k-1=4/6 | | In*(x-6)+In*(x-4)=In*15 | | 6x-9-4x=13 | | (4y+7)(4-y)=0 | | q(z)=pz+b | | ln*(x-5)+ln*(x-8)=ln*28 | | x-1/5=3-(x-9)/2 | | (150-80/1-x)2x=0 | | 40-(5)x=8+x | | (5-3x)2x=0 | | (4g-2)*(4g-2)=4 | | 3(2m-8)-4m=20 | | 2sinx=5+cosx | | 4.5=4t^2 | | 7x^2+7x=9 | | cos7x=cosx/3 | | 11-4+(-1)*5= | | 9t+18-3t-15= | | y=2x^4-4x^2+15 |

Equations solver categories